Wahdah Islamiyah’s Counter-Radicalism Strategy Through The New Media Network in Da’wah Development Of Palu City - Muhammad Khairil (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2018)
Radical labels and terrorist movements are often pinned down on various Islamic organizations in Indonesia, one of which is Wahdah Islamiyah (WI). This stigma is growing rapidly among Indonesians because the news in the media seems to accuse Islamic organizations of being the source of radical movements. Understanding the media becomes a crucial need in society. In addition, Islamic organizations are required to balance technological developments and utilize communication media in the modern era to re-establish the image of Muslims in Indonesia. This study focused on Wahdah Islamiyah in Palu City and was carried out with qualitative methods and case study approach to see and explain how the Wahdah Islamiyah in Palu City understood and utilized the media in responding to radical ideas that were often attached to Islamic organizations. This research shows that WI has a special strategy in responding to radicalism and has been able to utilize online media even though it is not yet optimal.